The Comparison of Pronunciation Error in Vowel Sounds Between Early Adolescence Learners and Mid Adolescence Learners in Foreign Language Learning - , admin; Amprih Cahya, Novi Candra (Jetlal, 2017)
This study using a quantitative design, causal comparative aimed to compare the pronunciation errors between Junior High School students and Senior High School students. As well as determine whether the early adolescence learners (junior high school students) have the ability of pronunciation better than mid adolescence learners (senior high school students), or otherwise. The study was conducted at VII A class of SMPN 1 Gresik around 29 students and X MIPA 7 class SMAN 1 Gresik around 29 students. The data in this study were collected through a test pronunciation by reading aloud. That includes two descriptive texts in the text there are 25 words that contain vowel sounds in English. The research found few differences in the number of pronunciation errors if Junior High School students tend to be morewrong in the pronunciation of a word and Senior High School students tend to be a little wrong in the pronunciation of words containing the vowel sounds. Pronunciation errors in students occur because the students do not know and do not mastered so much about vowel sounds. Particularly in the vowel sounds / É… /, / ei /, / u: /, / É…i /, / I /, / É… /, /eÆ/ and / Æ /.So, the students cannot pronounce the word correctly and the students cannot divided which the word must be pronounced with short vowel sounds and long vowel sounds. Result from this study is that the pronunciation of Senior High School students better than Junior High School students.